Physiological underpinnings of healthy brain ageing - Watt, Jodi K. (2022)
Changes in cerebral perfusion or metabolism can occur as a result of healthy ageing, and in conditions of impaired ageing such as mild cognitive impairment (MCI) or Alzheimer’s disease (AD). Overarchingly, this thesis aimed to explore physiological magnetic resonance imaging (MRI) measures to study both cerebral perfusion and metabolism in the healthy ageing brain. Specifically, arterial spin labelling (ASL) and functional magnetic resonance spectroscopy (1H-fMRS) were employed in the elucidation of healthy ageing.